Modifikasi Dan Uji Kinerja Mesin Pemarut Sagu Dengan Penggerak Motor Bensin Dan Pedal Sepeda - Saripudin Nur Ali; Toni Mulyono; Yosefina Mangera (Faculty of Agriculture, Musamus University, 2019)
This study aims is to modify the intake hopper, grater rollers, pedal drive motors, and find out the effective capacity of the modified grater and compare it to the unmodified shredder. The method used in this research is to make design, modification, and testing of tools and machines. Based on the results of research, Ali BK sago dissolution using a motorbike driven by Honda WZ 20 (old movers) produces pith as much as 3.25 kg /minutes, CPT National 5.5 HP 2200 rpm (new movers) driving motor produces pith as much as 5.90 kg/minutes with an average pith diameter of 0.4318 mm, and solubility using a bicycle pedal drive produces pith as much as 0.63 kg/minutes with an average pith diameter of 0.5410 mm. Making this sago sieve machine cost Rp. 4 242 000.